Combination of positron emission tomography/computed tomography and chest thin-layer high-resolution computed tomography for evaluation of pulmonary nodules: Correlation with imaging features, maximum standardized uptake value, and pathology. Issue 31 (August 2018) - Hou, Shasha; Lin, Xiaoyun; Wang, Shen; Shen, Yiming; Meng, Zhaowei; Jia, Qiang; Tan, Jian
Abstract : Abstract: This study aimed to analyze the imaging findings of 18 F-fluorodeoxyglucose positron emission tomography/computed tomography ( 18 F-FDG PET/CT) and chest thin-layer high-resolution computed tomography (HRCT), correlate the maximum standardized uptake value (SUVmax), and the pathological type of benign or malignant pulmonary nodules (PNs), and assess the diagnostic accuracy in differentiating malignant from benign PNs. A retrospective review of 18 F-FDG PET/CT scans from 88 patients with PNs confirmed by pathology or clinical follow-up were included. They both accepted PET/CT and HRCT scan conventional. The final results were determined by a combination of PET/CT and HRCT. Independent samples t test was used for statistical analysis. Receiver operating curves (ROC) were generated and the optimal threshold of SUVmax was determined. The sensitivity, specificity, and accuracy of HRCT, PET/CT, and PET/CT combined with HRCT in the diagnosis of PNs were 83.3%, 70%, 77.3%; 91.7%, 62.5%, 78.4%; and 95.8%, 75%, 86.4%, respectively. The SUVmax of malignant nodules was significantly higher than that of benign nodules, and the difference was statistically significant ( t  = –5.668, P  < .001). In the subgroup analysis, the SUVmax of squamous cell carcinoma was higher than that of the denocarcinoma ( t  = –5.442, P  < .001), and that of bronchioloalveolar carcinoma ( t  = 4.678, P  < .001), the difference were both statistically significant. There were both no significant difference between adenocarcinoma and bronchioloalveolar carcinoma ( t  = 0.36, P  = .722), tuberculosis and inflammatory nodules ( t  = –0.18, P  = .858). Higher the value of SUVmax, greater the risk of malignancy. However, when the SUVmax ranges between 2.5 and 8.0, the lesion may be benign or malignant, and a comprehensive evaluation using combination methods with HRCT are required. When SUVmax <2.5, there is still a 9.5% chance of PN malignancy. ROC curve shows SUVmax >3.635 as the best threshold, and the sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of PET/CT in diagnosis of PNs were 83.3%, 62.5%, 79.2%, 71.7%, and 71.4%, respectively. PET/CT combined with HRCT should be advocated to improve the sensitivity, specificity, and accuracy of PET/CT in diagnosis of PNs.